Fundamental immunological problems associated with "transmissible spongiform encephalopathies". Issue 2 (February 2015) - Ebringer, Alan; Rashid, Taha; Wilson, Clyde
Abstract "Bovine spongiform encephalopathy", "scrapie", as well as Creutzfeldt–Jakob disease and kuru belong to a group of related neurological conditions termed "transmissible spongiform encephalopathies". These diseases are based on the LD50 measurement whereby saline brain homogenates are injected into experimental animals and when 50% of them develop symptoms, this is considered as transmission of the disease, but the gold standard for diagnosis is autopsy examination. However, an untenable assumption is being made in that saline brain homogenates do not cause tissue damage but it is known since the time of Pasteur, that they give rise to "post-rabies vaccination allergic encephalomyelitis". This is the fundamental flaw in the diagnosis of these diseases. A way forward, however, is to examine infectious agents, such as Acinetobacter which show molecular mimicry with myelin and elevated levels of antibodies to this microbe are found in multiple sclerosis patients and animals affected by "bovine spongiform encephalopathy".